Massivste epigastrische Schmerzen bei einem 59-jährigen Patienten - Welland, S. (Internist (Berl), 2020)
Abdominal pain is a frequent cause of consultation to doctors’ offices and emergency rooms. The most common differential diagnoses can be confirmed with readily available, cost-effective, and low-risk diagnostic tools such as laboratory tests, ultrasound, or gastroscopy. Additional diagnostic tests are required to exclude rare causes such as small, solid, or hematological malignancies, metabolic disorders, or polyneuropathies of varying origin. In the following, we present the case of a patient with severe epigastric pain due to neuroborreliosis, and recapitulate the diagnostic steps for clarifying abdominal pain using this example.